Experimental and numerical investigation of concrete columns reinforced with frp bars - Guri, Zijadin (Faculty of Civil Engineering, UKIM, Skopje, 2018)
Presented in the considered doctoral dissertation are original experimental and numerical comparative investigations of the behavior of concrete bridge piers reinforced by use of plain or standard reinforcement and, alternatively, by use of composite FRP bars representing a new specific composite material. After the introductory Chapter 1 that provides a brief presentation of the subject and the objectives of the realized specific experimental and analytical investigations, there follows Chapter-2 in which are displayed the specific physical-mechanical characteristics of the FRP bars as a new specific composite material that has been used as an alternative material for reinforcement of the models of the experimentally tested concrete bridge piers. Chapter 3 shows the characteristics of the designed and built experimental models of bridge piers reinforced by use of classical reinforcement, and alternatively, by use of composite FRP bars. Presented additionally are the applied integral procedure and the specific experimental equipment used for the realization of the original experimental cyclic tests on the models of bridge piers up to deep nonlinearity, including also the failure stage. All experimental tests have been realized under simultaneous effect of constant vertical loads and monotonous incremental cyclic horizontal loads up to failure enabling realistic simulation of seismic forces during real earthquakes. Chapter 4 provides a consistent presentation of the obtained original experimental results from all realized experimental nonlinear tests on concrete bridge piers reinforced by classical reinforcement and, alternatively, by FRP bars as a specific composite reinforcement. The obtained experimental results show that the applied composite reinforcement may become a sound alternative for the classical reinforcement in future, particularly in realization of specific technological solutions in specific environments and conditions of construction. Chapter 5 shows the developed refined nonlinear analytical models by use of the most advanced software solutions based on the general concept of the finite element method by successful application of the formulated nonlinear three-dimensional finite elements. The formulated refined nonlinear analytical model has successfully been verified based on the obtained original experimental results from the realized nonlinear experimental tests on models of bridge piers reinforced with classical reinforcement and composite reinforcement composed of incorporated FRP bars with the role of longitudinal reinforcement. Presented in the next chapter, Chapter 6, is the practical application of the formulated refined three-dimensional analytical model for analysis of the nonlinear seismic response of a real bridge with central piers reinforced by classical reinforcement and, alternatively, by a reinforcement composed of composite FRP bars. The results obtained from the performed nonlinear seismic analyses under the effect of real earthquakes have confirmed the extraordinary generality and thoroughness of the formulated analytical models. The formulated refined nonlinear analytical models may successfully be used in expert analyses of the nonlinear behavior of bridge structures under very strong earthquakes in case their middle piers are reinforced by the new composite reinforcement composed of FRP bars. The last, Chapter 7, provides conclusions drawn from the realized integral research activities as well as general directions for future investigations in the considered specific research field.
Докторска дисертација одбранета во 2018 година на Градежниот факултет во Скопје, под менторство на проф. д–р Ѓорѓи Кокаланов.